«SIDE REACTIONS» TO VITAMIN AND MINERAL COMPLEXES AMONG CHILDREN - S.O. Klyuchnikov ("Paediatrician" Publishers LLC, 2007)
The article shows findings of the multi centered research, which has analyzed the application of the vitamins and vitamin and mineral complexes among children. Researchers questioned 9,296 parents from 9 Russian cities. Thus, the article shows that the most popular vitamin and mineral complexes of all 26 indicated in questionnaires are Multitabs, Pikovit and Alfavit, which have been chosen by 23,2, 14,9 and 13,1% of parents, respectively. smaller figures were registered for complivit (11,8%) and jungles (10,2%). in some cases, (Biovital Gel, Vitrum) the frequency of VMC application has depended on the region, where respondents reside, as well as on the age of the children. «side reactions» to VMCS were noted among 7,4-16,5% of children. Smallest recurrence of the «side reactions» to VMCS belonged to Alfavit, while the highest one - to Biovital Gel. Most «side reactions» were characterized as slight and manifested themselves in the form of the facial skin redness, rash and skin itch. Key words: children, vitamin and mineral complexes, side reactions.